The effort to increase the students’ interest in learning during the Covid-19 pandemic through comic media - Ru'iya, Sutipyo; Kistoro, Hanif Cahyo Adi; Sutarman, Sutarman; Maulana, Luthfi Ahmad (Universitas Muhammadiyah Magelang, 2021)
The Covid-19 pandemic has made humans adjust their behavior, especially in the world of education. Changes in learning activities from a face-to-face system to an online system, have a huge impact on students' psychology, especially on interest in learning. This mentoring activity was carried out through school student social media groups. The purpose of this assistance is to increase students' motivation and interest in learning which is decreasing using comics media. Through this activity, students' interest in learning and awareness of implementing health protocols has increased. Improvements in each disciplinary indicator in health protocols and interest in learning are as follows. First, disciplinary changes in health protocols with indicators using masks increased by 17%, washing hands increased by 9%, and social distancing increased by 20%. Second, the increase in motivation and interest in learning changes in the indicators, namely managing time increases by 30%, getting used to independent learning increases by 20%, and completion of tasks from teachers increases by 30%.